SUSTAINABILITY INDICATORS FOR WATER SECURITY - Sugahara, Cibele Roberta; Branchi, Bruna Angela; Lombardo Ferreira, Denise Helena [UNESP]; Mendes, Jakeline Pertile (Fundacao Univ Tocantins, 2022)
The present paper aims to highlight the importance of efficient water management on the choice of sustainability indicators based on an integrated environmental assessment model. The method chosen in this paper is descriptive with a qualitative approach. The data collected come from documents published by ANA and OECD. The work indicates that the indicators selected with the DPSIR model are appropriate for the management of water resources, but there are limitations. The application of the DPSIR approach confirmed its usefulness in the management of water resources and water security, guiding the identification of a set of indicators. The discussion of the properties of the sustainability indicators reveals that those based on the DPSIR model meet the fourth principle of the Bellagio STAMP. The DPSIR model applied to the management of water resources can contribute to the monitoring and security of water.
Keywords: Sustainability Indicators; Environmental Indicators; Water Security; Water Resources; DPSIR Model